1998
DOI: 10.1016/s0014-5793(98)00927-2
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induced by modified ribonucleosides in human cell culture systems

Abstract: The in vitro modulation of apoptosis and cell proliferation by modified in comparison with non-modified ribonucleosides was investigated for the first time using peripheral blood lymphoeytes, HL-60 cells and Caco-2 cells as human cell culture models. Modulating effects of several ribonucleosides were found in the range of 10-~-10 s mol/i. The following ribonuclensides induced significant apoptosis of HL-60 cells: adenosine, N6-dimethyladenosine, N~-(2-isopentenyl)-adenosine, N2-dimethylguanosine. A significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…6 The association with apoptosis-related GO terms is also in accord with previous studies. 5,7,8 The significant association of our gene list with the GO term ''unfolded protein response'' suggests that i 6 A could exert its in vitro biological effects by inducing cellular stress associated with an accumulation of unfolded proteins. Unfolded proteins can be correctly refolded by chaperone proteins or degraded by the ubiquitin-proteasome pathway; when levels of misfolded proteins are excessive, cells can die.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…6 The association with apoptosis-related GO terms is also in accord with previous studies. 5,7,8 The significant association of our gene list with the GO term ''unfolded protein response'' suggests that i 6 A could exert its in vitro biological effects by inducing cellular stress associated with an accumulation of unfolded proteins. Unfolded proteins can be correctly refolded by chaperone proteins or degraded by the ubiquitin-proteasome pathway; when levels of misfolded proteins are excessive, cells can die.…”
Section: Discussionmentioning
confidence: 98%
“…4 We previously showed that i 6 A exerts potent in vitro antitumour activity on human epithelial cancer cell lines derived from different types of tumours. 5 Several i 6 A mechanisms of action have been hypothesized, including inhibition of cell proliferation, 5 inhibition of protein prenylation, 6 induction of apoptosis, 7,8 inhibition of DNA, RNA and/or protein synthesis, 2,9 and inhibition of nucleoside transport. 10,11 However, the precise mechanism of action of i 6 A in inhibiting cancer cell proliferation in vitro remains to be clarified.…”
mentioning
confidence: 99%
“…It was observed that i6A antiproliferative effect was due to CDK1 and CDK2 inhibition. [7][8][9][10] Although the induction of apoptosis by i6A has been observed in some cancer cell lines, the mechanisms by which this compound induces apoptosis are generally unknown. It is well established that oxidative stress can activate the c-Jun N-terminal protein kinase (JNK) that is an important regulator in the cellular response to a variety of exogenous and endogenous stresses.…”
mentioning
confidence: 99%
“…Proteolysis may release these biogenic peptides during gastrointestinal transit or during food processing (for a review, see references 7, 20, and 30). These biological activities include opioid agonist and antagonist peptides, hypotensive peptides which inhibit angiotensin-I-converting enzyme (ACE), and mineral binding, immunomodulatory, antibacterial, and antithrombotic peptides (12,13,29). Generally, three strategies are used to identify and characterize biologically active peptides: (i) isolation from in vitro enzymatic digests of precursor proteins; (ii) isolation from in vivo gastrointestinal digests of precursor proteins; and (iii) chemical synthesis based on combinatorial library designs of peptides which have a structure identical to that of those known to be bioactive (4,30).…”
mentioning
confidence: 99%